Removing Formaldehyde‐Induced Peptidyl Crosslinks Enables Mass Spectrometry Imaging of Peptide Hormone Distributions from Formalin‐Fixed Paraffin‐Embedded Tissues. (30th September 2020) - Lee, Dong‐Kyu; Rubakhin, Stanislav S.; Kusmartseva, Irina; Wasserfall, Clive; Atkinson, Mark A.; Sweedler, Jonathan V.
Abstract: Linking molecular and chemical changes to human disease states depends on the availability of appropriate clinical samples, mostly preserved as formalin‐fixed paraffin‐embedded (FFPE) specimens stored in tissue banks. Mass spectrometry imaging (MSI) enables the visualization of the spatiotemporal distribution of molecules in biological samples. However, MSI is not effective for imaging FFPE tissues because of the chemical modifications of analytes, including complex crosslinking between nucleophilic moieties. Here we used an MS‐compatible inorganic nucleophile, hydroxylamine hydrochloride, to chemically reverse inter‐ and intra‐crosslinks from endogenous molecules. The analyte restoration appears specific for formaldehyde‐reactive amino acids. This approach enabled the MSI‐assisted localization of pancreatic peptides expressed in the alpha, beta, and gamma cells. Pancreatic islet‐like distributions of islet hormones were observed in human FFPE tissues preserved for more than five years, demonstrating that samples from biobanks can effectively be investigated with MSI. Abstract : The preservation of biological samples in formaldehyde induces intra‐ and inter‐crosslinking of peptides, which hampers the mass spectrometric detection of those analytes. Chemical reversal of formaldehyde‐induced peptidyl crosslinking permits mass spectrometry imaging of intact peptides, while protecting the spatiochemical characteristics of analytes in formalin‐fixed paraffin‐embedded tissues.